Triggering parental involvement for parents of different language backgrounds: the role of types of partnership activities and preschool characteristics. Issue 1 (2nd January 2016) - Hachfeld, Axinja; Anders, Yvonne; Kuger, Susanne; Smidt, Wilfried
Abstract : Home and educational institutions are children's most important external influences and a positive partnership between the two can positively affect children's cognitive and non-cognitive development. Quality of family–preschool partnership (FPP) can depend on preschool and family characteristics. For Germany, studies show that immigrant parents perceive a lack of positive FPP. The present study addresses the following research questions: (1) How do parents and teachers in Germany rate FPP? (2) Do ratings of FPP differ between parents who do or do not speak German at home? (3) Is there a relation between the structural quality of the centre and ratings of FPP for teachers and parents? Results reflect positive ratings of FPP (1). Mean comparisons confirmed differences between parent groups (2). Multilevel regression analyses indicate that percentage of children who do not speak German at home is positively associated with parents' ratings of FPP, but negatively with teachers' satisfaction about FPP (3).